Investigation of dose related effects of propolis on anxiety and some biochemical parameters with sympathetic skin response and increased T-maze - Nisari, Mustafa; Emre, Memet; Dolu, Nazan; Acer, Hale; Pektaş, Ferhat (Journal of Surgery and Medicine, 2020)
Aim: Propolis has been shown to have anti-microbial, antioxidant, anti-tumor, anxiolytic and anti-inflammatory effects. However, to the best of our knowledge, there are no studies on its anxiogenic effects. In this study, we aimed to investigate the effects of different doses of propolis on anxiety in rats with cold stress via sympathetic skin response (electrodermal activity) and elevated T maze. Methods: Forty Wistar albino male rats were used in the study, divided into four groups: The control group, low dose (10 mg/kg PRO), medium dose (30 mg/kg PRO) and high dose propolis groups (50 mg/kg PRO). Propolis was administered via gavage to all rats except the control group. Twenty minutes after injection, the anxiety scores of the rats were evaluated with an elevated T-maze, and their electrodermal activities (EDA) were measured. At the end of the experiment, some enzymatic and lipid values were measured with malondialdehyde (MDA) in blood samples. Results: The percentage of time spent on open arms and the number of open arm entries were lower in the 10mg/kg PRO group, while an increase was observed in the 30 mg/kg PRO group. EDA values were lower in the 30 mg / kg PRO (P=0.012; P=0.02, respectively) and 50 mg / kg PRO (P=0.013, P=0.02, respectively) groups as compared to the control group. MDA was significantly lower in the 30 mg/kg PRO and 50 mg/kg PRO groups. While AST value increased in the 30 mg / kg PRO group, ALT value decreased. Total cholesterol and triglyceride values were significantly lower in the 50 mg / kg PRO group. HDL value increased significantly after administration of propolis and LDL value decreased significantly only in the 10 mg/kg PRO group. Conclusions: According to the results obtained by EDA and T labyrinth methods, while low and high dose propolis, which was administered to rats after cold stress, showed an anxiogenic effect, medium dose propolis exerted an anxiolytic effect. It also decreased MDA values in the medium and high dose groups and influenced enzymatic and lipid values in favor of the rat. It was concluded that the anxiety-related effects of propolis were dose-dependent.